Colorado Paper - Method of Fixing Prices of Bituminous Coal Adopted by U. S. Fuel Administration (with Discussion) - C. Garnsey; J. H. Allport (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1920)
During the latter part of 1916 and the early months of 1917, due to war activities, there was a threatened shortage of coal which resulted in panic among consumers and a rush to obtain coal at once at any price. As a result of this insistent demand for immediate delivery, prices were bid up by the consumers to unprecedented heights; spot coal which had previously been selling at from $1.50 to $2 per ton was bid up to $5, $6, and, in exceptional cases, as high as $7.50 or more per ton. Then when the April, 1917, contract period arrived, contracts could be made only at prices ranging from $3 up to $5 and $6 per ton for the year's delivery. This condition caused such a demoralization of the business, and SO much complaint, that some action to regulate prices was considered essential by the National Administration. Lane-Peabody Agreement In May, 1917, a committee under the chairmanship of F. S. Peabody, of Chicago, was appointed by the Council of National Defense, through Mr. Lane, to consider the whole question of bituminous coal. This committee, with the Secretary of the Interior, Mr. Lane, after numerous meetings and long negotiations with the operators throughout the country, announced on June 29 an agreement between the Committee and the producers, fixing a tentative maximum price for bituminous coal throughout the country at $3 per net ton f.o.b. mines, to which was added 25 c. for selling commission to wholesalers. This plan was based on the idea of fixing a maximum price, high enough to greatly stimulate production, with the expectation that the laws of supply and demand would, with ample production, operate to maintain fair and just prices for coal throughout the country.